Effects of adding liquid lactose or molasses to pelleted swine diets on pellet quality and pig performance. Issue 2 (3rd April 2020) - Dunmire, Kara M; Wickersham, Tryon A; Frenzel, Leslie L; Sprayberry, Sarah R; Joiner, Logan C; Hernandez, Lily P; Cassens, Andrew M; Dominguez, Brandon; Paulk, Chad B
Abstract: Two experiments were conducted to evaluate the effects of including liquid lactose (LL) and molasses (M) in swine diets on pellet quality and pig performance. In experiment 1, a total of 194 nursery pigs (DNA 241 × 600, initially 6.7 ± 0.4 kg at 27 d of age) were used in a 33-d experiment evaluating the effects of LL (SweetLac 63; Westway Feed Products, Tomball, TX) or cane molasses on nursery pig performance and pellet quality. Pelleted experimental diets were fed from d 0 to 21, and a common pelleted diet fed from d 21 to 33. Dietary treatments consisted of a control diet containing 19.1% total sugars from whey powder and whey permeate and experimental diets with a percentage of whey permeate replaced by either 5% or 10% LL or 9.4% cane molasses (5 LL, 10 LL, and 9.4 M, respectively). Hot pellet temperature and production rate decreased ( P < 0.05) from the control to 9.4 M treatments with 5 LL and 10 LL having intermediate effects. Pellet durability index (PDI) increased ( P < 0.05) in 5 LL, 10 LL, and 9.4 M, respectively. From d 0 to 7, pigs fed the 10 LL and 9.4 M treatment had the best G:F followed by the control and 5 LL treatments. From d 0 to 21, ADFI had a marginally significant improvement ( P < 0.10) in pigs fed up to 10 LL in the diet. Fecal consistency scores at d 7 were also firmer ( P < 0.05) in pigs fed 9.4 M compared with pigs fed the control or 5 LL treatments with pigs fed the 10 LL treatment being intermediate. There was no evidence for differences in fecal consistency scores for d 14. In experiment 2, a total of 289 finishing pigs (DNA 241 × 600; initially 53.5 ± 0.5 kg BW) were used in a 53-d experiment evaluating the effects of LL on pellet quality and finishing pig performance. Experimental diets were fed in pelleted form from d 0 to 53 divided into three phases. Dietary treatments were a corn-soybean meal control diet with 0%, 2.5%, 5%, and 7.5% LL added in the place of corn. PDI improved (linear, P < 0.01) with increasing inclusion of LL. There were no differences in ADG, ADFI, final BW, or carcass characteristics. Pigs fed diets with increasing levels of LL tended to have improved (quadratic, P = 0.070) G:F.